Promotion of breastfeeding on primary education: integrative review - Fernanda Demutti Pimpão Martins; Luciana Pedrosa Leal; Tatiane Gomes Guedes; Marly Javorski; Cleide Maria Pontes (Universidade Federal de Goias, 2016)
This study aims to analyze the approaches on breastfeeding promotion in primary education. This is an integrative review carried out on BVS, PUBMED, SCOPUS, CINAHL, COCHRANE and SciELO, which found 1,598 publications with seven of them selected for the final sample. Categories identified - Approaches to knowledge, perceptions, beliefs and experiences of breastfeeding from children's perspective: the interviews revealed knowledge and beliefs unfavorable to breastfeeding; - Approach to the breastfeeding promotion content in primary education: the content is superficially addressed in textbooks and educators state they do not teach it in class. The approach to breastfeeding in primary education has been varied, although reduced, especially in relation to educational interventions. Nurses need to expand this approach, with active and playful methodologies, with a view to impacting the future of the next generations.